The Matter of Quebec Movement: A Review on Canadian Domestic Politics - Al-hasin, FIkry Muhammad Reza; Kusumaningrum, Demeiati Nur (Nation State: Journal of International Studies, 2020)
The Canadian government has succeeded to maintain its political stability by implementing middle-ways approach to face the separatism movement. Parti Quebecois has been the biggest promoter of Quebec sovereign movement. This political party has held referendums to be independent from the central government and managed to gain public attention. This paper aimed to figure out how the series of Quebec sovereign movements affected Canadian domestic politics. It used constructivist approach to explain why the Quebec struggle for independent and how its strategies influence the Canadian domestic structure. The data obtained from library research. This paper examines the effort of Quebec movement consist of (1) creating a political discourse of “self-determinantion”. The social movement transforms into Québécois political party and it visioned to gain territory of the province since the decade of the 1960s; (2) social construction dealing with the issue of French identity as non-Canadian culture. The supports of the idea embedded in the several forms of regulations and propaganda in the public sphere.